Produksi Pengetahuan Seksualitas : Representasi Pelecehan Seksual Remaja Di Puger - Nur Idayati; Maulana S. Kusumah (Faculty of Social Science, Universitas Negeri Malang, 2020)
In this article that focuses on issues of youth, sexuality and sexual harassment. The existence of culture in the reality of adolescent habits about permitting sexual harassment behavior. Besides sexuality is still considered taboo to be discussed in public spaces. Sociologically this phenomenon can be said as a form of failure of the construction of sexuality in adolescents. This assumption is supported by the knowledge of adolescent sexuality that allows sexual harassment and is considered a joke. Sexuality as a production of knowledge is taken from the point of view of adolescents and environments that have direct relations. The discourse of sexuality comes with a variety of operators. This article is the main issue narrated using the knife of Michel Foucault's analyst about sex, power and knowledge. In addition this study aims to describe the knowledge of adolescent sexuality in Puger. In its methodological consequences this article uses the Foucault genealogy to narrate the knowledge of adolescent sexuality. Researchers try to see how basic problems that arise can be solved by a historical framework. Then the key informants were teenagers / students from junior high schools (Public Schools) and senior high schools (Religious Schools) in Puger Kulon.